A Theorem on the Commutative Neutrix Product of Distributions - Fisher, Brian; Öz¸ça, E.; Gülen, Ü. (Sarajevo Journal of Mathematics, 2024)
The commutative neutrix products f_+(x) · δ ^(r)(x) and f_-(x) · δ ^(r)(x) are evaluated for r=0,1,2,…, where f is a function which is infinitely differentiable on an open interval containing the origin and f_+(x) =H(x)f(x) and f_-(x) =H(-x)f(x), H denoting Heaviside's function. 2000 Mathematics Subject Classification. 46F10